Abnormal left atrial compliance is associated with a history of life-threatening arrhythmia in corrected Tetralogy of Fallot - Vautier, Mathilde; Mulet, Benoit; Macquaire, Clémence; Cousergue, Cynthia; André, Camille-Océane; Maragnes, Pascale; Ollitrault, Pierre; Labombarda, Fabien (Frontiers in Cardiovascular Medicine, 2023)
Objectives The objectives of this study were to examine left atrial (LA) function and compliance using two-dimensional (2D) strain analysis in adult patients with corrected Tetralogy of Fallot (c-ToF) and to investigate the relationships between LA function and patient characteristics, especially history of life-threatening arrhythmia (h-LTA). Methods Fifty-one c-ToF patients (34 males; age, 39 ± 15 years; h-LTA, n=13) were included in this retrospective monocenter study. In addition to a 2D standard echocardiography examination, 2D strain analysis was performed to assess left ventricular (LV) and LA functions, including peak-positive LA strain (LAS - reservoir function) and LA compliance (defined as the ratio LAS/(E/Ea)). Results Patients with h-LTA were older and exhibited a longer QRS duration. LV ejection fraction, LAS and LA compliance were significantly lower in the group of patients with h-LTA. Indexed LA and RA volumes, RV end-diastolic area was significantly higher and RV fractional area change significantly lower in the h-LTA group. LA compliance was the best echocardiographic predictor for h-LTA (AUC: 0.839; p < 0.001). Moderate inverted correlations were found between LA compliance and age and QRS duration. Among the echocardiographic parameters, LA compliance was moderately inversely correlated with RV end-diastolic area (r = -0.40, p = 0.01). Conclusion We documented abnormal LAS and LA compliance values in adult c-ToF patients. Further study is needed to determine how best to incorporate LA strain, particularly LA compliance, into multiparametric predictive models for LTA in c-ToF patients.